FLUOROQUINOLONES IN PEDIATRIC PATIENTS: NO MORE "OFF-LABEL USE". Issue 1 (14th December 2015) - Dinavitser, Natalie; Berlin, Maya; Miller, Reuven; Finkel-Pekarsky, Victoriya; Berkovitch, Matitiahu
Abstract : Fluoroquinolones (FQs) are used in pediatric patients worldwide. However, due to cartilage damage in young animals they are not approved for children under 18 years of age for most indications. Major regulatory authorities such as EMA, FDA, UK, Ireland, NZ and Australia indicate that FQs are contraindicated in children. Ciprofloxacin and levofloxacin can be prescribed to children, but only for a few indications. As a result, FQs are used "off-label" in this population. From our experience, we believe that FQs should not be contraindicated in children. However, evidence-based data is needed. Objective: To investigate whether FQ use in children may cause musculoskeletal adverse reactions (ADRs). Methods: We reviewed the Israel Ministry of Health ADR reporting system and VigiLyze (WHO reporting system) for musculoskeletal ADRs due to FQs in children. A literature search– Medline, Pubmed, Cochraine database and pharmacologic textbooks, for musculoskeletal ADRs among FQ treated pediatric patients was conducted. Terms used: Fluoroquinolones, ciprofloxacin, levofloxacin, ofloxacin, arthropathy, tendinophaty, arthralgia, children, pediatric use. Results: During the period 1968 to Feb 2015, the Israeli MOH did not receive spontaneous reports regarding FQs in children. The VigiLyze program identified 192 ADR reports in children related to FQs: arthralgia, arthropathy, myalgia, and tendon injury. Most ADRs were transient and reversible. The literature search indicated that although musculoskeletal ADRs are not uncommon, they are mild, transient, and not necessarily due to FQs. Joint MRI, performed in some of the studies, did not reveal cartilage damage. Conclusions: FQs should be registered for pediatric patients as for adults.